An Investigation into the Use of Stimulant Therapy during Pregnancy. (6th September 2012) - Shields, Natalie; Muza, Rexford; Kosky, Christopher; Williams, Adrian J.
Abstract : Introduction . A lack of documentation of stimulant use during pregnancy means that doctors have difficulty advising narcoleptic and hypersomnolent patients. Objectives . To investigate the use of stimulant therapy in narcoleptic and hypersomnolent patients during pregnancy. Method . A search of clinic letters at a tertiary sleep clinic identified women who became pregnant whilst receiving stimulant therapy between 01/09/1999 and 18/11/2010. Fifteen patients were included in a telephone survey. Results . There were 20 pregnancies. The reported advice received with regards to stimulant use was variable. In 7 pregnancies, medication was stopped preconceptually: 1 had a cleft palate and an extra digit 6 had good foetal outcomes. In 8 pregnancies, medication was stopped postconceptually: 1 had autism and attention-deficit hyperactivity disorder; 7 had good foetal outcomes. In 5 pregnancies, medication was continued throughout pregnancy: 2 ended in miscarriage; 1 was ectopic; 2 had good foetal outcomes. The most common symptom experienced was debilitating hypersomnolence. Conclusion . There are no standardised guidelines for use of stimulants during pregnancy. Women have significant symptoms during pregnancy for which there is an unmet clinical need. More research is needed into whether medication can be safely continued during pregnancy, and if not, when it should be discontinued. Better standardized advice should be made available.